Enhanced Cognitive Walkthrough: Development of the Cognitive Walkthrough Method to Better Predict, Identify, and Present Usability Problems - Lars-Ola Bligård; Anna-Lisa Osvalder (Advances in Human-Computer Interaction)
To avoid use errors when handling medical equipment, it is important to develop products with a high degree of usability. This can be achieved by performing usability evaluations in the product development process to detect and mitigate potential usability problems. A commonly used method is cognitive walkthrough (CW), but this method shows three weaknesses: poor high-level perspective, insufficient categorisation of detected usability problems, and difficulties in overviewing the analytical results. This paper presents a further development of CW with the aim of overcoming its weaknesses. The new method is called enhanced cognitive walkthrough (ECW). ECW is a proactive analytical method for analysis of potential usability problems. The ECW method has been employed to evaluate user interface designs of medical equipment such as home-care ventilators, infusion pumps, dialysis machines, and insulin pumps. The method has proved capable of identifying several potential use problems in designs.